Notch1 Has an Important Role in β-Cell Mass Determination and Development of Diabetes - Eom, Young Sil (Diabetes Metab J, 2021)
BACKGROUND: Notch signaling pathway plays an important role in regulating pancreatic endocrine and exocrine cell fate during pancreas development. Notch signaling is also expressed in adult pancreas. There are few studies on the effect of Notch on adult pancreas. Here, we investigated the role of Notch in islet mass and glucose homeostasis in adult pancreas using Notch1 antisense transgenic (NAS). METHODS: Western blot analysis was performed for the liver of 8-week-old male NAS mice. We also conducted an intraperitoneal glucose tolerance test (IPGTT) and intraperitoneal insulin tolerance test in 8-week-old male NAS mice and male C57BL/6 mice (control). Morphologic observation of pancreatic islet and β-cell was conducted in two groups. Insulin secretion capacity in islets was measured by glucose-stimulated insulin secretion (GSIS) and perifusion. RESULTS: NAS mice showed higher glucose levels and lower insulin secretion in IPGTT than the control mice. There was no significant difference in insulin resistance. Total islet and β-cell masses were decreased in NAS mice. The number of large islets (≥250 µm) decreased while that of small islets (<250 µm) increased. Reduced insulin secretion was observed in GSIS and perifusion. Neurogenin3, neurogenic differentiation, and MAF bZIP transcription factor A levels increased in NAS mice. CONCLUSION: Our study provides that Notch1 inhibition decreased insulin secretion and decreased islet and β-cell masses. It is thought that Notch1 inhibition suppresses islet proliferation and induces differentiation of small islets. In conclusion, Notch signaling pathway may play an important role in β-cell mass determination and diabetes.